2003
DOI: 10.1194/jlr.m300103-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

Sphingomyelinase D, a novel probe for cellular sphingomyelin

Abstract: Sphingomyelin (SM) and free cholesterol (FC) are concentrated in the plasma membranes of eukaryotes; however, the physiological significance of their association is unclear. A common tool for studying the role of membrane SM is digestion with bacterial sphingomyelinase (SMase) C, which hydrolyzes SM to ceramide. However, it is not known whether the observed effects of SMase C treatment are due to the loss of SM per se or to the signaling effects of ceramide. In this study, we tested SMase D from Corynebacteriu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
18
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 40 publications
4
18
0
Order By: Relevance
“…All ceramides and SMase C (S. aureus, 174 units/mg) were purchased from Sigma Chemical Co (St. Louis, MO). SMase D (Corynbacterium pseudotuberculosis) was purified from transfected E.Coli as described previously [15]. The SMase activities were assayed using the Amplex Red SMase Kit from Invitrogen Inc. Ceramide phosphate was prepared by the action of SMase D on egg SM and PE, as described before [16].…”
Section: Methodsmentioning
confidence: 99%
“…All ceramides and SMase C (S. aureus, 174 units/mg) were purchased from Sigma Chemical Co (St. Louis, MO). SMase D (Corynbacterium pseudotuberculosis) was purified from transfected E.Coli as described previously [15]. The SMase activities were assayed using the Amplex Red SMase Kit from Invitrogen Inc. Ceramide phosphate was prepared by the action of SMase D on egg SM and PE, as described before [16].…”
Section: Methodsmentioning
confidence: 99%
“…DMAPP (1S,2R)-D-erythro-2-(Nmyristoylamino)-1-phenyl-1-propanol) was purchased from Biomol (Plymouth Meeting, PA, USA). SMase D was purified from E.Coli transfected with the C. pseudotuberculosis SMase D by affinity chromatography, as described earlier [6]. The transfected E. Coli were obtained from Dr. Stephen Billington, University of Arizona.…”
Section: Methodsmentioning
confidence: 99%
“…Several studies showed that hydrolysis of plasma membrane SM by bacterial SMase C (which degrades it to ceramide) results in a rapid translocation of plasma membrane cholesterol to endoplasmic reticulum (ER), as evident from the stimulation of acyl CoA: cholesterol acyltransferase (ACAT) reaction [4,5]. Our previous studies in human foreskin fibroblasts showed that unlike the effect of SMase C, treatment of the cells with SMase D (which degrades SM to ceramide phosphate) results in relatively modest stimulation of ACAT, although the extent of SM hydrolysis by the two enzymes was comparable [6]. This raised the possibility that the cellular response to SMase C treatment with respect to cholesterol trafficking is at least partly due to the generation of ceramide rather than the loss of SM alone from the PM.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations